33‐1: Invited Paper: Development of AMOLED Display: From Rigid to Flexible. Issue 1 (May 2016) - Huang, Xiuqi; Hu, Kun; Lin, Li; Shan, Qi; Yang, Xiaolong; Gao, Xiaoyu
Abstract : Recently, rigid AMOLED display industry has stepped into mass production stage progressively. Meanwhile, flexible display has attracted more attention for its great potential to generate novel product market. However, when it comes to the mass production, flexible AMOLED display still faces quite a few technological challenges. In this paper, a 4.6sdtp2016471408inch AMOLED display which can be rolled up under bending radius less than 3mm has been demonstrated, using process compatible to the current rigid AMOLED mass production line.